Strategy Development of Low-Cost Airlines in South Africa - Wolmarans, Barry (My University, 2014)
This study was undertaken to establish the current strategies and strategies available to the low-fare airlines of South Africa. The research was based on a qualitative methodology, based on 11 respondents over 9 interview sessions, the data was analysed using thematic content analyses. The incumbent low-fare airlines during the period of research were faced with a market which had shrunk in size, a reported over capacity and major increases in some of the base costs such as fuel and airport taxes, which placed significant pressure on yields, with two airlines reporting loses and one airline exiting the market. The key driver to sustainability of the low-fare airlines in South Africa, has been shown to be the reduction in costs, by implementing revenue management technology to monitor all aspects of the operations, introduce modern fuel efficient fleets, and expand operations by code share and alliances. A current gap in the low-cost business model within the South African context is the lack of secondary airports suitable for the operation of the current fleet. It has been suggested through the interview process that a cost advantage would be generated for an airline to operate out of these secondary airports. Additional recommendations that were developed were the initiatives to widen distribution channels through social media and alliance and code share agreements that would assist in generating higher passenger volume. A modern fleet would provide a lower cost basis, which would allow for lower fares or higher margins.
MBA thesis
Keywords: Low cost airlines; Strategy development